Peran Program Rancang Bangun Wadah Cuci Tangan dalam Meningkatkan Kesadaran Higiene dan Proteksi terhadap Pandemi Covid-19 di Desa Kute Bakti, Aceh Tenggara - Arhami, Arhami; Masri, Masri; Husaini, Husaini; Suhaeri, Suhaeri; Thaib, Anwar (Universitas Syiah Kuala, 2023)
The problem of the Corona Virus Disease 2019 (COVID-19) started at the end of 2019 when it first appeared in Wuhan, China. It was reported that by July 2020, COVID-19 had become a pandemic that spread to 193 countries, including Indonesia. Although the severe outbreak of the COVID-19 pandemic has started to subside over time, it is important to acknowledge that another pandemic might occur. This paper aims to contribute to the efforts of preventing and controlling the COVID-19 pandemic outbreak by implementing health protocols. The health protocol in question includes three important measures: handwashing, mask-wearing, and avoiding crowds, collectively known as the